Child Development in a Changing World : Risks and Opportunities - Boyden, Jo; Dercon, Stefan; Singh, Abhijeet (Oxford University Press on behalf of the World Bank, 2017)
This review explores current understandings of child development and the consequences for children of risk exposure in low- and middle-income countries by integrating empirical evidence from development economics with insights from allied social science disciplines. It provides a holistic perspective that highlights the synergies between children's developmental domains, drawing particular attention to dimensions such as self-efficacy, self-esteem and aspirations, which have had only limited treatment in the economics literature to date, especially in developing countries. It concludes that there is strong evidence of dynamic relationships between risk factors in early childhood and later outcomes across multiple developmental domains, emphasizing the heightened effect of shocks to the care environment and the cumulative effect of multiple shocks. It also concludes that risk is distributed unevenly, with children who are both in poverty and disadvantaged socially according to, for example, their ethnicity bearing the greatest burden; within a household, gender, birth order and other factors mean that some suffer disproportionately from shortfalls and incomplete protection. However, this review finds that low endowments in early childhood can be at least partially compensated for through improved environments and investments in later childhood, emphasizing the resilience of some children. The review goes on to explore the impact on children of dramatic socio-economic changes that have occurred in recent years with rapid growth across most developing countries. It highlights four key forces for change—fall in absolute poverty, increased access to services, changing household incentives for investing in children, and changing social and cultural values—and stresses the ambiguous effects on the welfare of children and their long-term prospects. In so doing, the review aims to consolidate emerging evidence on how risks and opportunities for child development may have changed in these dynamic contexts.